The Awareness Assessment Process - Mantau, Márcio J.; Benitti, Fabiane B. V. (Anais do Simpósio Brasileiro de Sistemas Colaborativos (SBSC); 2025: Anais do XX Simpósio Brasileiro de Sistemas ColaborativosDO - 10.5753/sbsc.2025.6574, 2025)
Different strategies in the literature seek to help support awareness mechanisms in collaborative applications. However, the most common approaches are projected to a specific context and do not focus on evaluating these mechanisms or the provided support from the user’s point of view. Few studies present methods or processes that provide awareness aspects in collaborative systems; thus, finding a good starting point in the literature can be challenging for beginners in awareness design. We evolve the findings presented by (MANTAU; BENITTI, 2023a), providing contributions towards developing an awareness assessment process that allows accessing the awareness and, consequently, the collaboration support through measuring awareness mechanisms from the participant’s viewpoint. Then, we expose the model’s artifacts to HCI and collaborative system examiners’ appreciation to verify the suitability of the process by reliability and usefulness criteria.